An approximation to the language ideologies of pewenche speakers from the Biobío Region (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article examines the main linguistic ideologies that the bilingual speakers of two Pewenche communities build around chedungun. This exploratory study has a qualitative approach. The analyzed data correspond to the speech of 20 bilingual speakers between 18 and 75 years old, belonging to the rural communities of Pitril and Butalelbun from Alto Biobío. In general, the results show that chedungun is conceived as the main composing element for the maintenance of ethnic spirituality and identity. Moreover, we have discovered language purist ideologies that foster linguistic insecurity in the youngest speakers of Pitril.
Keywords: Language ideologies; pewenche; bilingual; chedungun